The Influence of Human Support on the Effectiveness of Digital Mental Health Promotion Interventions for the General Population - Renfrew, Melanie Elise; Morton, Darren Peter; Morton, Jason Kyle; Przybylko, Geraldine (Frontiers in Psychology, 2021)
Mental wellbeing amongst the general population is languishing—exacerbated by the Coronavirus Disease 2019 (COVID-19) pandemic. Digital mental health promotion interventions (DMHPIs), that improve mental health literacy and encourage adoption of evidence-informed practical strategies are essential. However, attrition and non-adherence are problematic in digital interventions. Human support is often applied as an antidote; yet, there is a paucity of randomized trials that compare different human support conditions amongst general population cohorts. Limited trials generally indicate that human support has little influence on adherence or outcomes in DMHPIs. However, providing participants autonomy to self-select automated support options may enhance motivation and adherence.